Use of Anti-TNF Alpha Blockers Can Reduce Operation Rate and Lead to Growth Gain in Pediatric Crohn's Disease - Woo, Min Hyung (Pediatr Gastroenterol Hepatol Nutr, 2019)
PURPOSE: Pediatric Crohn's disease (CD) is directly related to growth and has a high probability of requiring surgical intervention(s); therefore, more active treatment for CD is required for children. This study investigated the impact of biologics on growth and disease course associated with surgery. METHODS: This was a retrospective cohort study involving patients diagnosed with CD at the Seoul National University Children's Hospital (Seoul, Korea) between January 2006 and October 2017. The aim was to determine the characteristics of pediatric patients with CD and whether biologics affected growth and the surgical disease course. RESULTS: Among patients who underwent surgery for CD, the mean number of operations per patient was 1.89. The mean time from initial diagnosis to surgery was 19.3 months. The most common procedure was fistulectomy (34%), followed by incision and drainage (25%). In all patients, the use of biologics increased the height (p=0.002) and body mass index (BMI) (p=0.005). Among patients who underwent surgery, height (p=0.004) and BMI (p=0.048) were increased in the group using biologics. Patients who used biologics exhibited a low operation rate only within 2 years after diagnosis, with no differences thereafter (p=0.027). CONCLUSION: Although biologics could not mitigate the operation rate in pediatric patients who underwent surgery for CD, biological therapy delayed disease progression within 2 years of disease onset. Additionally, biologics conferred growth and BMI benefits in this window period. Therefore, it may be helpful to use biologics for optimal growth in pediatric patients with a high probability of undergoing future surgery.